INFLUENCE OF THE CALCULATED LENGTH OF ELEMENTS ON THE CRITICAL PARAMETERS OF STABILITY OF FRAME-BAR STRUCTURAL SYSTEMS - Gennadievich, Emelyanov Sergey; Valerievich, Dubrakov Sergey; Olegovna, Dubrakova Ksenia (Journal of Applied Engineering Science, 2020)
This article examines the effect of changing the design length of the elements of frame-bar structural systems operating in a constrained bifurcation. For the criterion of the form of buckling of an element of a frame-bar structural system, the sign of the work of end moments and shear forces is taken. Using this criterion, an expression was obtained to assess the effect of changing the calculated length of the frame struts on the critical parameters of the entire system, which allows varying the geometry of the structure to influence its performance.A two-span frame is considered, in which the central pillar is loaded with a concentrated force Pcr, and the outer pillars are loaded with forces αRcr. The type of bifurcation of the rods (constrained or forced) and the critical parameters of the stability of the system before and after changing the calculated length of its elements are determined.Changes in the design length of elements that passively lose stability do not have a significant effect on the critical stability parameters of the frame-bar structural system. At the same time, a 30% decrease in the calculated length of the struts in an active bifurcation leads to a decrease in the critical force by 50%.The presented rather simple algebraic dependencies allow obtaining a qualitative and quantitative assessment of the effect of the calculated length coefficient on the stability of frame-rod structural systems made of wood. It has been established that the conditions for securing elements that passively lose stability do not have a significant effect on the critical parameters of the system.
Keywords: stability, frame-rod system, active bifurcation, passive bifurcation, calculated length